Pariwisata dan Identitas Perempuan Banjar: Suatu Analisis Sosiologi dalam Cerpen Gadis Pasar Terapung - Setia Budhi (Jurnal Sosiologi Andalas, 2023)
This article is about the identity of Banjar women in South Kaliantan in literary works. Literary studies on tourism have not been studied much. A qualitative study on the case of the short story "Galuh Pasar Terapung", offers a study of the sociology of literature using a literary tourism approach. The results of the study cover three perspectives, namely the analysis of tourism themes or discourse in literary works, literary activities in tourism places and literature as tourism promotion.